The Transformation of Laozi and Zhuangzi Ideas in Chinese Literati Aesthetics - Diemantaitė, Ieva (Acta Orientalia Vilnensia, 2002)
The goal of the article is to reveal the transformation of ideas of the founders of classical Taoism - Laozi and Zhuangzi in influential Chinese literati (wenrenhua) aesthetics. Current investigation is based on the authentics sources of classical Taoism (“Laozi” and “Zhuangzi“) and aesthetic writings of the Chinese literati Gu Kaizhili “Lun Hua”, “Hua Yuntaishan ji”, Wang Wei (415-445) “Xu hua”, Zong Bing “Hua shanshui xu”, Xie Hes “Guhua pinlu”, Wang Wei (701-761) “Shanshui jue” and “Shanshui lun”, Shi Tao “Kugua heshang hualu”, that: tractates of Su Sh, Mi Fu, Ni Zan, Zhao Mengfu, Dong Qichang and others. Leaning on the main Taoist principles (Tao, ziran (spontaneity), qi (vitality), pu (simplicity), shen (spirit), xu (emptiness) and so on) and literati aesthetic categories (qi (vitality), yi (idea), shen (spirit), ziran (spontaneity), pu (simplicity) and their combinations (zhuan shen, shenqi, shengqi and so on), the author makes a conclusion that ideas of Laozi and Zhuangzi seem to have determined the latest extensive development of literati art and aesthetics.